2009
DOI: 10.1016/j.ejmech.2008.10.033
|View full text |Cite
|
Sign up to set email alerts
|

4-Phenoxybutoxy-substituted heterocycles – A structure–activity relationship study of blockers of the lymphocyte potassium channel Kv1.3

Abstract: The voltage-gated potassium channel Kv1.3 constitutes an attractive pharmacological target for the treatment of effector memory T cell-mediated autoimmune diseases such as multiple sclerosis and psoriasis. Using 5-methoxypsoralen (5-MOP, 1), a compound isolated from Ruta graveolens, as a template we previously synthesized 5-(4-phenoxybutoxy)psoralen (PAP-1, 2) which inhibits Kv1.3 with an IC50 of 2 nM. Since PAP-1 is more than 1000-fold more potent than 5-MOP, we here investigated whether attaching a 4-phenoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…When attaching the 4-phenoxybutoxy side chain of PAP-1 to other planar heterocyclic systems, we had observed that phenoxyalkoxypsoralen-type Kv1.3 blockers have a very steep structure-activity relationship and that the coumarin system cannot be replaced (Bodendiek et al, 2009). Our model explains these structure-activity findings and the Hill coefficient of 2 and shows that the coumarin rings of two PAP-1 molecules are located in the inner pore but do not block ion permeation per se.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…When attaching the 4-phenoxybutoxy side chain of PAP-1 to other planar heterocyclic systems, we had observed that phenoxyalkoxypsoralen-type Kv1.3 blockers have a very steep structure-activity relationship and that the coumarin system cannot be replaced (Bodendiek et al, 2009). Our model explains these structure-activity findings and the Hill coefficient of 2 and shows that the coumarin rings of two PAP-1 molecules are located in the inner pore but do not block ion permeation per se.…”
Section: Discussionsupporting
confidence: 55%
“…These results suggest that the ether oxygens are very important for PAP-1 activity and explain why compound SB9 (Fig. 3) is ϳ4.5 times more active than its analog 1,2-dihydro-N-methyl-4-(4-phenoxybutoxy)quinolin-2-one (SB4) (Bodendiek et al, 2009), in which the ether oxygen is replaced by an N-CH 3 group (Fig. 3).…”
Section: Potassium Channel Block By Cationophilic Ligands 593mentioning
confidence: 94%
See 3 more Smart Citations